Voltage stability assessment using PMUs and STATCOM - Suresh Babu Palepu; Manubolu Damodar Reddy (Institute of Advanced Engineering and Science, 2023)
Since the previous few decades, researchers and utilities have been extremely concerned about voltage instability because to the numerous instances of system blackouts caused by voltage instability that have been recorded in various regions of the world. With the development of synchro phasor technology, it appears conceivable to track and manage the system's voltage stability in real time. This study suggests using phasor measuring units (PMUs) placed strategically to monitor voltage stability margin online and to regulate it using a static synchronous compensator (STATCOM). According to the minimum reactive and real power loanability for the most of the line outages, STATCOM has been installed at the critical bus. Based on the difference between the bus voltage and its reference value, STATCOM supplies reactive power into the bus. PMU measurements are used to determine bus voltages at regular intervals, and reactive power is then added to the bus online as necessary. The increased voltage stability margin brought on by STATCOM injecting reactive power is continuously checked. Based on simulations performed on the IEEE 14-bus system and the New England 39-bus system, the effectiveness of the suggested approach for online monitoring and management of voltage stability margin (VSM) has been proven.